Cyber Public Relations Sadewa Market dan Interaktivitas Penggiat UMKM di Jawa Tengah - Hasna, Sofia (Tuturlogi: Journal of Southeast Asian Communication, 2020)
Sadewa Market UMKM website is one of the alternative public services in Central Java with empowerment programs on UMKM. Sadewa Market functioned as a means for cyber public relations in the digital age. This article seeks the activities of Cyber Public Relations on the Sadewa Market Website and the extent to which interactivity is built between the government and the community. Through case studies, this research was conducted with interviews and observations to the central Java provincial government and UMKM actors throughout 2017-2018. This study revealed that the Cyber PR Activity of Sadewa Market UMKM Website is intended to increase interactivity between the Central Java Provincial Government and UMKM activists. Cyber PR activities are driven by the Dinas Koperasi & UMKM of Central Java Provincial Government through attracting visitors, engagement & dialogue, defensive/crisis, and building campaigns.  The digital assistance page on the Website of Sadewa Market encourages interactivity, integration, and information publication. Public engagement is part of Cyber PR activities by emphasizing feedback and asymmetric communication. There are several notes on Cyber PR Website activities, namely regular media monitoring programs, social listening, and content design activities for the formation of public opinion. These notes need to be considered so that Cyber PR activities can be consistent and sustainable.